Numerical Simulation and Experimental Validation of the Microindentation Test Applied to Bulk Elastoplastic Materials - Cruchaga-Ssa., M (2012)
The main objective of this work is to compare numerically simulated loadindentation depth curves together with deformation and stress fields underneath a sharp indenter for a set of mystical materials. Firstly, a numerical simulation and experimental validation of the microindentation test applied to three different bulk elastoplastic materials (copper, stainless steel and pure aluminium) using two indenters (Berkovich and spherical) are presented. The simulation of these microindentation tests is carried out using the finite element large strain elastoplastic and contact models. The corresponding results are particularly aimed at addressing the following aspects: the influence of the indenter geometry on both the loadindentation depth curve and range of plastic strains involved in the test, the comparison of the 3D results for the sharp indenter with those of the 2D approximation, the capabilities of the modelling through experimental validation of the numerical predictions and, in addition, an assessment of the indentation size effect. Secondly, the numerical results of Berkovich indentation applied to a set of mystical materials are exhaustively discussed. Although it is effectively shown that these mystical materials exhibit indistinguishable loadpenetration depth curves during the loading phase, an important aspect that has not been previously addressed is that some clear differences in their responses are obtained for the unloading stage. Finally, the deformation and stress contours at the maximum indentation force and after unloading are particularly analysed. © 2012 IOP Publishing Ltd.